2017
DOI: 10.1080/09500693.2017.1356943
|View full text |Cite
|
Sign up to set email alerts
|

Student experience of school science

Abstract: This paper presents the findings of a two-phase mixed methods research study that explores the link between experiences of school science of post-16 students and their decisions to take up science for their higher studies. In the first phase, students aged 16-17 (n = 569) reflected on the past five years of their school science experience in a quasi-longitudinal approach to determine a typology of experiences. The second phase entailed data collection through interviews of a sample of these students (n = 55) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 31 publications
3
44
0
7
Order By: Relevance
“…Teaching science to students is a challenging and complicated process (Fleischner et al, 2017;Kadbey, Dickson, & McMinn, 2015;Omorogbe & Ewansiha, 2013). The reason is that science is considered a cluster of difficult (Buah & Akuffo, 2017;Etobro & Fabinu, 2017) and boring subjects (Shirazi, 2017). Besides, teachers must be aware that science learning often involves the fundamental knowledge that has been brought by students (Arends, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Teaching science to students is a challenging and complicated process (Fleischner et al, 2017;Kadbey, Dickson, & McMinn, 2015;Omorogbe & Ewansiha, 2013). The reason is that science is considered a cluster of difficult (Buah & Akuffo, 2017;Etobro & Fabinu, 2017) and boring subjects (Shirazi, 2017). Besides, teachers must be aware that science learning often involves the fundamental knowledge that has been brought by students (Arends, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The attitude toward science is declining as well (Abrahams, 2007;Haste, 2004). The most frequently mentioned reasons are that science subjects are not relevant and are isolated from pupils' everyday lives ) and therefore are perceived as difficult (Lyons, 2006;Shirazi, 2017) and boring (Ebenezer & Zoller, 1993;. In contrast, some studies revealed that lessons in some science disciplines (especially biology) are relatively popular among pupils (Prokop, Prokop & Tunnicliffe, 2007) and biological topics, such as human health, are more interesting for the pupils than technological science (da Silva et al, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Vi savner mer kunnskap om elevers opplevelser av arbeidsmåter som brukes i undervisningen. Det finnes forskning som gir en del svar på hvilke arbeidsmåter elever ønsker og ikke ønsker (Juuti, Lavonen, Uitto, Byman, & Meisalo, 2010;Klepaker et al, 2007;Osborne & Collins, 2001;Raved & Assaraf, 2011;Shirazi, 2017;Toplis, 2012), men vi mener det er behov for mer dybdekunnskap om elevbegrunnelser for hvorfor de foretrekker noen arbeidsmåter fremfor andre. Ifølge Juuti et al (2010) er det behov for forskning som gir økt forståelse av sammenhengen mellom elevers synspunkter på arbeidsmåter, og utvikling av interesse for naturfag i skolen.…”
Section: Forskningsspørsmålene Våre Erunclassified
“…Slik informasjon sammenholdt med forskning på elevers laering i naturfag kan bidra til utvikling av faget i skolen. Dette kan igjen påvirke naturfaglig allmenndanning og rekruttering til yrker som krever naturfaglig kompetanse (Shirazi, 2017).…”
unclassified